THE EFFECT OF KANGAROO MOTHER CARE ON PROMOTING BREASTFEEDING, WEIGHTING AND DURATION OF HOSPITALIZATION IN PREMATURE INFANTS IN IRAN - Parsa, Parisa; Karimi, Simin; Roshanaei, Ghoddatalah (Journal of Postgraduate Medical Institute, 2020)
Objective: To find out the effect of Kangaroo Mother Care (KMC) on weight gain, breastfeeding and duration of hospitalization in premature infants. Methodology: This was a quasi-experimental research. One hundred premature infants were selected by convenience method. They were randomly allocated to the experimental (50 infants) and the control (50 infants) groups. In the experimental group, the babies were provided minimum of one hour KMC position. In the control group, conventional care was given in incubator. The data collection tool was a questionnaire including demographic characteristics, frequency of breast-feeding, weight gain and length of hospital stay. Comparison of groups was carried out with independent t-test, chi-square test and ANOVA. Results: There was no difference between the two groups before intervention (control: 1789.80 vs. experimental: 1757.90, P=0.660). Repeated measurements ANOVA showed difference between mean weight of newborns over time in the two groups (F=32.45, p <0.001). Hospital stay in the intervention group was shorter (control: 26.7 days vs. experimental: 14.3, P <0.001). The frequency of breastfeeding in the experimental group was significantly more than in the control group (control: 5.04 vs. experimental: 13.32, P <0.001). Conclusion: KMC improves the neonatal weight gain, breastfeeding and decreases duration of hospitalization.